Development of Entrepreneurship-Based Mathematical E-Module and Its' Learning with PBL to Improve Students' Mathematical Problem Solving Ability (Department of Mathematics, Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the validity of the entrepreneurship-based mathematics E-Module, the practicality and effectiveness of learning mathematics with the PBL model assisted by the entrepreneurship-based mathematics E-Module to improve students' mathematical problem solving abilities. This research is a development research with the ADDIE model which is applied to class XI of SMK Negeri 1 Lemahabang, Cirebon Regency. The results showed that the entrepreneurship-based mathematics E-Module was declared valid with a percentage of the E-Module value of 92.88% in the